Alcohol consumption and risky sexual behaviour amongst young adults in a low-income community in Cape Town. (March 2014) - Adams, Sabirah; Savahl, Shazly; Carels, Cassandra; Isaacs, Serena; Brown, Qunita; Malinga, Mandisa; Monageng, Boitumelo; Zozulya, Maya
<x xml:space="preserve">Abstract</x> Aims: The aim of the study was to explore alcohol use and risky sexual behaviour among young adults in a low-income community in Cape Town. Design and setting: The study followed a descriptive correlational design within a quantitative methodological framework. More specifically, a participatory research model was employed in collaboration with young people attending a secondary school in the participating community. Data collection: The street-intercept method was used to administer a structured questionnaire consisting of the Alcohol Use Disorders Identification Test and the Self-Report Risky Sexual Behaviours Scale. Findings: A key finding of this study contributes to the established body of research demonstrating a significant relationship between alcohol consumption and RSB (r = 0.48; p ≤ 0.01; N = 143). Another crucial finding of the study indicates that a substantial amount of the participants are classified as either harmful drinkers (Males = 20.0%; Females = 17.8%) or being alcohol dependent (Males = 54.3%; Females = 47.9%). Conclusions: These statistics are a typical reflection of drinking behaviour in impoverished communities in Cape Town and South Africa in general. The findings display the exigency for interventions to start at both the primary and secondary school level to counter the effects and consequences of alcohol consumption and risky sexual behaviour among young adults in this community.